(E) and (Z)-1, 4-Diphenyl-2-(2-phenyl-1H-benzo[d]imidazol-1-yl)but-2-ene-1, 4-dione. (27th May 2014) - Ahmed, Sarfaraz; Mir, Niyaz A.; Shah, Tariq A.; Raza, Waseem; Muneer, M.; Rath, Nigam P.
Abstract : The title compound C29 H20 N2 O2 adoptsE andZ geometry about olefinic C14–C22 bond, where the benzoyl group at C22 and benzimidazole group at C14 lie on the opposite sides and on the same side across the olefinic bond, respectively. InE configuration the phenyl groups of both benzoyl moieties are almost perpendicular to benzimidazole ring while the phenyl of benzimidazole at C7 is oriented at an angle of 30.76 (5)° to the mean plane of the benzimidazole ring. On the other hand inZ configuration the phenyl group at C7 of benzimidazole ring is oriented at an angle of 38.44 (7)° to the mean plane of the benzimidazole ring while the phenyl rings of benzoyl moieties at C15 and C23 lie at an angle of 16.07 (9)° and 40.29 (6)°, respectively, to the mean plane of the benzimidazole ring. The observed bond distances and bond angles fall within the normal accepted range of values.